An efficient and provable secure identity-based identification scheme in the standard model - Ji-Jian, Chin; Swee-Huay, Heng; Bok-Min, Coi (SPRINGER-VERLAG BERLIN, 2008)
We present an efficient and provable secure identity-based identification scheme in the standard model. Our proposed scheme is secure against impersonation under passive attack based on the Computational Diffie-Hellman assumption, and secure under active and concurrent attacks based on the One-More Computational Diffie-Hellman assumption.